2012
DOI: 10.1007/s10198-012-0395-6
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide for multiple myeloma: cost-effectiveness in patients with one prior therapy in England and Wales

Abstract: LEN/DEX is a cost effective oncology therapy from the perspective of the NHS for MM patients with one prior treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
0
21
2
1
Order By: Relevance
“…Among the selected studies, the results were most sensitive to the cost of the novel agents ( n = 6) and the hazard ratios for overall survival ( n = 3) . Only half of these economic studies considered the variation in utility values when conducting deterministic sensitivity analyses. Indeed, the results from one of the studies were sensitive to this factor …”
Section: Resultsmentioning
confidence: 99%
“…Among the selected studies, the results were most sensitive to the cost of the novel agents ( n = 6) and the hazard ratios for overall survival ( n = 3) . Only half of these economic studies considered the variation in utility values when conducting deterministic sensitivity analyses. Indeed, the results from one of the studies were sensitive to this factor …”
Section: Resultsmentioning
confidence: 99%
“…However, according to recent evidence, combination therapy with lenalidomide–dexamethasone may be a cost-effective option for the treatment of patients with rrMM in several European countries and settings 16,36,37. Concerning Greece, to the best of our knowledge, this is the first pharmacoeconomic study undertaken to compare these two agents.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials demonstrated that lenalidomide, for example, increased expected QALYs from 1.5 to 3.7 for patients requiring second-line treatment. (16)…”
Section: Multiple Myeloma Case Studymentioning
confidence: 99%
“…In 2004, patients requiring second-line therapies often used dexamethasone or a combination of thalidomide and dexamethasone as a second-line treatment. (16) Once lenalidomide and bortezomib came onto the market, however, almost all non-responders received one of these therapies within a few years. By 2009, 67% of all multiple myeloma prescriptions written were for drug regimens using lenalidomide or bortezomib.…”
Section: Multiple Myeloma Case Studymentioning
confidence: 99%